2023
DOI: 10.3390/land12061137
|View full text |Cite
|
Sign up to set email alerts
|

A Participatory Approach to Assess Social Demand and Value of Urban Waterscapes: A Case Study in San Marcos, Texas, USA

Abstract: Waterscapes can have meaningful benefits for people’s wellbeing and mental health by helping them feel calmer and more connected to nature, especially in times of stress such as the COVID-19 pandemic. The waterscapes along the San Marcos River (Texas, USA) provide economic, social, environmental, and emotional benefits to the surrounding community. To assess the social demand for and emotional experiences in these blue spaces, we used a new framework called Blue Index that collects noncontact data from photo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…Firstly, the elderly showed a highest CER toward clean emotion. This finding is aligns with a study of social needs and values of urban water features, which confirmed that a positive correlation between perceptions of cleanliness and higher positive emotion of happiness, serenity, surprise, and relaxation, and significantly influenced the six basic human emotions of joy, serenity, fear, disgust, sadness, and surprise [54]. Also, a study on the perceived visual landscape quality of green spaces has demonstrated that the healthy and tidy trees with appropriate color contrasts are more conducive to the restoration of human perception [55].…”
Section: The Effect Of Color Characteristic On Positive Cersupporting
confidence: 90%
“…Firstly, the elderly showed a highest CER toward clean emotion. This finding is aligns with a study of social needs and values of urban water features, which confirmed that a positive correlation between perceptions of cleanliness and higher positive emotion of happiness, serenity, surprise, and relaxation, and significantly influenced the six basic human emotions of joy, serenity, fear, disgust, sadness, and surprise [54]. Also, a study on the perceived visual landscape quality of green spaces has demonstrated that the healthy and tidy trees with appropriate color contrasts are more conducive to the restoration of human perception [55].…”
Section: The Effect Of Color Characteristic On Positive Cersupporting
confidence: 90%
“…An equal number of studies examine personal motivation as a variable (n=29, 49%). Individuals visit urban riversides primarily for physical exercise, recreation and leisure, including activities such as walking or jogging, cycling, swimming, dancing, skateboarding, rowing, dragon boat racing, water marathons, dog walking, picnicking, dining, photography, social gatherings, commuting, chess, and camping (e.g., Chen & Ma, 2023;Gargiulo et al, 2020;Guo et al, 2022;Gong et al, 2019;Liu et al, 2023;Meng et al 2020;Vierikko & Yli-Pelkonen, 2019;wade et al, 2023;Wu et al, 2019a;Yu et al, 2022;Zhang et al, 2022b;Zingraff-Hamed et al, 2022). Furthermore, two studies also discussed the motivation for restoration (Gargiulo et al, 2020;Jakstis et al, 2023).…”
Section: Personal Attributesmentioning
confidence: 99%
“…Green and blue spaces (GBSs) account for the majority of frequent visits to nature in a city, which function as ecological infrastructures that provide ESs to promote public health and wellbeing [24][25][26][27]. The psychological and mental benefits obtained from experiences with GBSs can further result in preventing anxiety [28], depression [25], chronic disease [26], and the impact of air pollution [29,30]. These effects were mainly detected for visitors exposed to GBSs in parks, communities, and streets in built-up regions of the host city [31].…”
Section: Introductionmentioning
confidence: 99%